(untitled) (University Journal of Zoology, Rajshahi University, 2012)
The research work was conducted to find out the seasonal occurrence of parasites of the major carp, Cirrhina mrigala from different water bodies of Rajshahi district during April 2009 to January 2010. A total of 95 fishes were examined of which 72 fishes were infected. Thirteen species of parasites viz. Trichodina pediculatus, Chilodonella cyprini, Ichthyophthirius multifiliis, Apiosoma sp., Dactylogyrus vastator, Gyrodactylus elegans, Hirudo sp., Argulus foliaceus, Lernaea sp. Phyllodistomum agnotum, Eucreadium sp., Camallanus ophiocephali and Pallisentis sp. were recorded from the infected fishes. Among all the parasites G. elegans was the most dominant parasite and skin had been found as the most vulnerable site for parasitic infestation. The maximum infestation was observed in winter season and the minimum infestation was observed in rainy season. Key words: Cirrhina mrigala; parasite; prevalence; abundance; mean intensity; infestation. DOI: http://dx.doi.org/10.3329/ujzru.v29i1.9465 UJZRU 2010; 29(1): 47-50